Is Social Work Still Racist? A Content Analysis of Recent Literature. Issue 4 (22nd August 2018) - Corley, Nicole A; Young, Stephen M
Abstract: Addressing systems of oppression that disproportionately affect racial and ethnic minoritized groups appears to be of marginal interest in social work's professional literature. This article describes the content analysis of articles on Asian Pacific Islander (API) Americans, African Americans, Latinx or Hispanic Americans, and Native or Indigenous Americans in four major social work journals published between 2005 and 2015. (The analysis serves to update a 1992 article by Anthony McMahon and Paula Allen-Meares that examined literature between 1980 and 1989.) Of the 1, 690 articles published in Child Welfare, Research on Social Work Practice, Social Service Review, and Social Work over an 11-year period, only 123 met the criteria for inclusion. Findings suggest that social work researchers are still failing to address institutional racism and are relying heavily on micro-level interventions when working with minoritized groups. Social workers need to increase efforts to dismantle institutional racism.